Developing a metadata application profile for the daily hire labour - Sen, Sangeeta (2018)
EMPOWER SSE is a Fundação para a Ciência e Tecnologia (FCT, Portugal) and Department of Science & Technology (DST, India), financed research project that aims to use the Linked Open Data Framework to empower the Social and Solidarity Economy (SSE) Agents. It is a collaborative project between India and Portugal that is focused on defining a Semantic Web framework to consolidate players of the informal sector, enabling a paradigm shift. The Indian economy can be categorized into two sectors: formal and informal. The informal sector economy differs from the formal as it is an unorganized sector and comprised of economic activities that are not covered by formal arrangements such as taxation, labor protections, minimum wage regulations, unemployment benefits, or documentation. The major economy in India depends on the skilled labor of this informal sector such e.g. daily labor, farmers, electricians, food production, and small-scale industries (Kalyani, 2016). The informal sector is mainly made of skilled people that follow their family job traditions, sometimes they are not even formally trained. This sector struggles with the lack of information, data sharing needs and interoperability issues across systems and organizational boundaries. In fact, this sector does not have any visibility to the society not having the possibility to do business as most of the agents of this sector do not reach the end of the chain. This blocks them from getting proper exposure and a better livelihood.